Prevalence of elevated levels of homocysteine (hyperhomocysteinemia) in patients with chronic kidney disease undergoing hemodialysis - Rizaldy Taslim Pinzon; Bulan Marchellia Wijaya; Esdras Ardi Pramudita; Nining Sri Wuryaningsih; Purwoadi Sujatno (National Scientific Medical Center, 2019)
Background: Chronic kidney disease is a disease with kidney damage of more than 3 months. Chronic kidney disease has five stages, in which in the fifth stage the patient requires renal replacement therapy. Hemodialysis replaces kidney function to get rid of waste substances, this process can also reduce the substances that the body may still need such as vitamins that can be wasted. Even the metabolism in the body will be disrupted, one of which causes the balance of homocysteine ​​metabolism to be disrupted. This causes homocysteine ​​levels to increase in the plasma. Objectives: To measure the prevalence of elevated homocysteine ​​levels (hyperomocysteinemia) in patients with chronic kidney disease who undergo hemodialysis. Methods and subjects: This is a cross sectional study with number of respondents in this study amounted to 91 people who all had chronic kidney disease undergoing hemodialysis at Bethesda Hospital and Panti Rapih Hospital in Yogyakarta. The selection of subjects used the consecutive sampling method. The data analysis used is univariate analysis. Results: Of the total 91 subjects with chronic kidney who undergo hemodialysis, 28.6% of them were elderly patients with an average age of 51.78 years, with men 59 subjects (64.8%) and women 32 subjects (35.2%). In all subjects got a history of hypertension and anemia 78 respondents (85.7%), diabetes 31 subjects (34.1%) and cancer 1 subjects (1.1%). The prevalence of subjects with hyperhomocysteinemia was 80 subjects (87.9%) and 11 were not (12.1%). In hyperhomocysteinemia patients (freq=80), 23 of them were elderly patients (88.5%), with men 55 subjects (93.2%) and women 25 subjects (78.1%). The history of the disease patients with hyperhomocysteinemia is anemia and hypertension 69 respondents (88.5%), diabetes 28 subjects (90.3%) and cancer 1 subject (100%). Conclusion: The prevalence of hyperhomocysteinemia in patients with chronic kidney disease undergoing hemodialysis is 87.9%.